Meningkatkan Mutu Pendidikan Melalui Pembelajaran Bahasa Arab Berbasis ICT - Isnol Khotimah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
Human resoursces are an asset that will always be useful in every generation. In order to create better human resources, it is necessary to increase the quality of better education. This increase was not spared by technology that was already rampant. It can be said that students today can enjoy the use of technology at home and at school. For that, it is very possible to apply technology-based learning in the scope of learning. The purpose of applying technology within the scope of learning is to improve the quality of education in order to increase student interest in learning. Keyword: Education, Technology, Learning